ANALYSIS OF THE FACTORS THAT CAUSE INDUCTION OF LABOR IN A MATERNITY MOTHER AT PMB MASSIANA SINTANG IN 2025 - Yunida Haryanti; Lea Masan; Rizki Amartani; Paskalia Tri Kurniati; Novin Yetiani; Yolanda Montessori (Prosiding Seminar Nasional Indonesia, 2025)
World Health Organization (WHO) data on national health status in achieving the Sustainable Development Goals (SDGs) target states that globally around 830 women die every day due to complications during pregnancy and childbirth, with a MMR rate of 216 per 100,000 live births (WHO, 2017). As many as 99% of maternal deaths due to pregnancy, childbirth or birth problems occur in developing countries. The MMR ratio is still considered quite high as targeted to be 70 per 100,000 live births by 2030.Research Objective: To determine the Analysis of the causes of labor induction in maternal birth. Research Methods: This study used a descriptive retrospective, data collection using secondary data.Results: An overview of the factors causing labor induction in maternal birth, based on uterine inertia that is 73 mothers (94%), Early Amniotic Disease that is 68 mothers (87%), based on serotinus that is 46 mothers (58%). Suggestion: It is expected to detect early what are the causes of labor induction